2020
DOI: 10.1177/0002764220952126
|View full text |Cite
|
Sign up to set email alerts
|

Sociotechnical Transformative Effects of an ICT Project in Rural Bangladesh

Abstract: The purpose of this article is to provide lessons from the field about an Information and Communication Technology for Development (ICT4D) project (Participatory Research and Ownership With Technology, Information and Change [PROTIC]) concerned with the use of mobile phones by women in remote villages in Bangladesh. The Bangladeshi government considers that the role of ICT in social and economic transformation is significant for the country’s development. International nongovernmental organizations (NGOs) also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…We know that the PROTIC women have been able to make effective use of information, for instance about modern agricultural practices in their farming and livestock production, and that they have been using both their newly acquired knowledge and traditional agricultural knowledge to solve problems (Stillman et al , 2020). The workshop showed that participants have some basic IL skills.…”
Section: Discussionmentioning
confidence: 99%
“…We know that the PROTIC women have been able to make effective use of information, for instance about modern agricultural practices in their farming and livestock production, and that they have been using both their newly acquired knowledge and traditional agricultural knowledge to solve problems (Stillman et al , 2020). The workshop showed that participants have some basic IL skills.…”
Section: Discussionmentioning
confidence: 99%
“…In the Bangladesh context, StillmanSarrica [26] have recently found that mobile phone usage has facilitated the transformation in attitudes, skills, and practices associated with rural women. On the other hand, due to a lack of infrastructure and other issues, rural people are easily subjected to the digital divide.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The PROTIC project was a collaboration between Australian researchers and Oxfam in Bangladesh, which aimed at empowering Bangladeshi women working in agriculture in remote communities through access to information (Stillman et al. , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%